Pengaruh Work Life Balance terhadap Employee Engagement dan Kepuasan Kerja sebagai Variabel Intervening pada CV Multi Agro Sarana - Syelvy, Sweethenia; Siddiq, Andhika Mochamad (Jurnal Ilmu Sosial, Manajemen, Akuntansi dan Bisnis, 2024)
Human resources are important assets that can be trained and developed to achieve company goals effectively. Employees who are highly engaged in their work have the potential to make more excellent contributions. Therefore, companies with high levels of Employee Engagement will experience increased productivity and efficiency. This study aims to identify factors influencing employee engagement, focusing on work-life balance and job satisfaction as intervening variables at CV Multi Agro Sarana. A questionnaire was used on 56 employees, and data was analyzed using Path Analysis. The results showed that work-life balance positively and significantly influences job satisfaction and employee engagement. Job satisfaction also has a positive and significant impact on employee engagement. This analysis indicates that the level of job satisfaction is a direct and indirect factor in the influence of Work-Life Balance on the level of employee engagement. Therefore, it can be concluded that improving Work-Life Balance can increase Employee Engagement, ultimately maximizing employee potential at CV Multi Agro Sarana and increasing company profits